An unusual presentation of dermatomyositis: dermatomyositis sine dermatitis presenting with rapidly progressive myositis - M. C. P. Madurapperuma; T. Poobalasingam; S. R. Constantine; M. De Silva; H. Karunatilake (Sri Lanka College of Internal Medicine, 2024)
Dermatomyositis sine dermatitis (DMSD) is a rare variant of dermatomyositis where progressive muscle weakness presents without the characteristic rash but with muscle histology of dermatomyositis. A 55-year-old woman presented with progressive severe proximal limb, neck, pharyngeal and respiratory muscle weakness, without dermatologic manifestations. Elevated muscle enzymes and myopathic electromyogram pointed towards inflammatory myositis while the muscle biopsy confirmed DMSD. Her condition improved with steroids, intravenous immunoglobulin, methotrexate, and rituximab. This case emphasises the necessity of maintaining a high index of suspicion for dermatomyositis, even when a classic skin rash is absent and the criticality of early aggressive treatment. Anti-NXP-2 antibody positivity could indicate severe disease.